Talking about interaction*. Issue 131 (November 2019) - Reeves, Stuart; Beck, Jordan
Highlights: There are disagreements in HCI over what is meant by 'interaction' and whether 'interaction' is a useful concept going forward. We review two diverging perspectives on 'interaction': seeking its definition, or dispensing with it. We chart a third way: 'interaction' has use as a promiscuous concept that helps glue together HCI communities, therefore argue for its retention, but with a 'therapeutic' attitude. Abstract: Recent research has exposed disagreements over the nature and usefulness of what may (or may not) be Human–Computer Interaction's fundamental phenomenon: 'interaction'. For some, HCI's theorising about interaction has been deficient, impacting its capacity to inform decisions in design, suggesting the need either to perform first-principles definition work or broader administrative clarification and formalisation of the multitude of formulations of the concepts of interaction and their particular uses. For others, there remain open questions over the continued relevance of certain 'versions' of interaction as a useful concept in HCI at all. We pursue a different perspective in this paper, reviewing how HCI treats interaction through examining its 'conceptual pragmatics' within HCI's discourse. We argue that articulations of the concepts of interaction can be a site of productive conflict for HCI that for many reasons may resist attempts of formalisation as well as attempts to dispense with them. The main contribution of this paper is in specifying how we might go about talking of interaction and the value of interaction language as promiscuous concepts .